SUCCESSFUL MEDICATION THERAPY OF ACUTE RIGHT VENTRICLE INSUFFICIENCY IN RECIPIENT WITH SIGNIFICANT PULMONARY HYPERTENSION AFTER HEART TRANSPLANTATION - A. M. Chernyavskiy; D. V. Doronin; A. V. Fomichev; M. N. Deryagin (Вестник трансплантологии и искусственных органов)
Acute right ventricular failure in the early period after orthotopic heart transplantation is a severe complication and can often lead to a fatal outcome. This is especially important in patients with high pulmonary arteries resistance. Drug therapy has shown effectiveness only for the treatment of primary pulmonary hypertension. Patient K., 23 years old with signifi cant pulmonary hypertension (mean pulmonary artery pressure of 60 mm Hg, PVR – 6 Wood units) underwent orthotopic heart transplantation. Acute right ventricular failure occurred at early postoperative period which required multicomponent inotropic support. In order to reduce resistance of the pulmonary circulation the patient received sildenafi l (daily dose 50 mg) in combination with inhaled Ventavis (5 mcg a dose every 3 hours) and receipt of Tracleer (bosentan) (at a dose of 125 mg per day). Complex drug therapy resulted in reduction of right ventricular failure, normalization of biochemical parameters. Invasive pulmonary artery pressure decreased to 30 mm Hg and pulmonary vascular resistance was 1.1 Wood units at the moment of discharge. We also revealed right ventricle end-diastolic volume reduction from 70 ml to 62 ml and ejection fraction of the right ventricle (RV EF) increased from 47,7% to 62% in 2 months. Our clinical observation demonstrates the high effi ciency of acute right heart failure complex therapy including inotropic agents in combination with drugs that reduce the pulmonary vascular resistance.